2010
DOI: 10.3109/00365521003632576
|View full text |Cite
|
Sign up to set email alerts
|

The study on the role of inflammatory cells and mediators in post-infectious functional dyspepsia

Abstract: Dyspepsia may occur after an acute onset of gastroenteritis in a part of patients. Potent chemicals derived from mast cells and ECs, including histamine, tryptase and 5-hydroxytryptamine may be involved in the pathogenesis of post-infectious functional dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 33 publications
0
60
1
4
Order By: Relevance
“…This finding is consistent with higher levels of GDNF in patients with functional dyspepsia 79 . Both duodenal and gastric biopsy samples showed mast cell hyperplasia and an increased release of histamine and tryptase (which indicates mast cell activation) 81 . Gastric biopsy samples also revealed a closer association between nerves and mast cells 81 , and these immune mediators are known to synergistically activate neurons 82 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with higher levels of GDNF in patients with functional dyspepsia 79 . Both duodenal and gastric biopsy samples showed mast cell hyperplasia and an increased release of histamine and tryptase (which indicates mast cell activation) 81 . Gastric biopsy samples also revealed a closer association between nerves and mast cells 81 , and these immune mediators are known to synergistically activate neurons 82 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
“…Both duodenal and gastric biopsy samples showed mast cell hyperplasia and an increased release of histamine and tryptase (which indicates mast cell activation) 81 . Gastric biopsy samples also revealed a closer association between nerves and mast cells 81 , and these immune mediators are known to synergistically activate neurons 82 . In the duodenal bulb, the number of chromogranin A (CGA)-positive enteroendocrine cells was reduced in duodenal biopsy samples from patients with functional dyspepsia, mostly in patients with EPS 83 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
“…The report is sufficient to show that a nutritional and intestinal pathogenesis lies behind malnutrition, persistent diarrhea as well as behind overall subclinical inflammation that is in turn associated with overweight. These dysfunctions depend on a positive energy balance in the associated, parallel-alternative forms of insulin resistance and fattening [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The intestinal pathogenesis consists of an overgrowth of immunogenic bacteria [1,9,12,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that these changes may contribute to symptom generation, either by direct interaction with nociceptive pathways or by infl uencing the normal physiology (including delayed gastric emptying and impaired gastric accommodation). On the other hand, low-grade lymphocytic and neutrophil infi ltration in the antral mucosa and increases in other infl ammatory components including enterochromaffi n-like cells and mast cells have been observed by others, suggesting that changes in histamine, tryptase, and 5-hydroxytryptamine (5-HT) could be biological mechanisms inducing gastro intestinal disturbances aft er gastrointestinal infections (38) . In addition, these investigators observed in postinfectious dyspepsia the numbers of activated mast cells and enterochromaffi ne cells in close proximity to the nerves to be signifi cantly higher than in those with nonspecifi c functional dyspepsia or controls.…”
Section: Pathophysiology Of Postinfectious Dyspepsiamentioning
confidence: 99%